Adjuvant immunotherapy in early-stage resectable non–small cell lung cancer: A new milestone - Tang, Wen-Fang; Ye, Hong-Yu; Tang, Xuan; Su, Jian-Wei; Xu, Kang-Mei; Zhong, Wen-Zhao; Liang, Yi (Frontiers in Oncology, 2023)
Currently, chemotherapy is the standard adjuvant treatment for early-stage non-small cell lung cancer (NSCLC). However, adjuvant cisplatin-based chemotherapy after surgery has been shown to improve 5-year survival rates by only 4−5%. Immunotherapy using immune checkpoint inhibitors (ICIs) has revolutionized the treatment of advanced NSCLC, there is a growing interest in the role of immunotherapy in early-stage NSCLC. Here, we summarize the rationale for adjuvant immunotherapy, including the postoperative immunosuppressive environment and immunological effects of platinum chemotherapy. Many ongoing clinical trials and the related progress in adjuvant immunotherapy in early-stage resectable NSCLC are discussed. Furthermore, we highlight several unresolved challenges, including markers predictive of treatment benefit, the efficacy of treatment for some oncogene-addicted tumors, the optimal combination therapy, the duration of adjuvant immunotherapy, and optimal selection between neoadjuvant and adjuvant immunotherapy. Early findings in some clinical trials are promising, and updated overall survival results will be useful for validating the current role of adjuvant immunotherapy, particularly in the context of perioperative strategy.